FAKTOR YANG MEMPENGARUHI MINAT BELI SOVENIR DI OBJEK WISATA TANJUNG LAPIN DESA TANJUNG PINANG KECAMATAN RUPAT UTARA - Thabrani "; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Tanjung Lapin Tourism Object is a tourist attraction located in North Rupat District. The decline in the income of people who sell souvenirs in Tanjung Lapin Tourism Objects has the traders to lose their jobs. This is caused by the souvenirs not have the hallmark of the local area, and making the tourists are not interested to buy. Then the offered souvenirs has no many choices and not have a good quality. This study was conducted to determine the factors that influence the buying interest of souvenirs and constraints faced in increasing the buying interest of souvenirs. Data obtained from interviews with Pokdarwis Chairman, traders and tourists visiting Tanjung Lapin tourist attraction. Then the data obtained were analyzed by using an interactive model consisting of three steps: data reduction, data presentation, and conclusion. Research shows that the souvenirs have no artistic touch, no regional characteristics, no charm, no good quality and relatively expensive price. This leads has a decline in the income of people who sell souvenirs. Keywords: Interest, Buy, Souvenir, Tourist Attraction